International Conference on “Earthquake Hazard and Risk in the Mediterranean Region”, Lefkoşa, Turkish Republic of Northern Cyprus, 18-22 October, 1999 (Lefkoşa)
2 cilt (1. c. [26], 648, [4] sayfa ; 2. c. [26] sayfa, sayfa 649-1085, [4] sayfa)